Family Nursing Competency of Student Nurse at Boromarajonani College of Nursing Nakhon Lampang, Thailand - เรณูรส, จักรวาล; วีระศิริ, เสาวคนธ์ (Journal of Health Science of Thailand, 2020)
This descriptive research was aimed at studying family nursing competency among student nurse at Boromarajonani College of Nursing Nakhon Lampang. Population consisted of 155 student nurses and 20 instructors. The questionnaire was used to collect data. The study tool was developed based on the concept of general family nursing competency of International Family Nurses Association and Thailand Nursing and Midwifery Council. The content validity was assess by 5 experts, and the CVI was 0.80. The tool was tried out with similar group of 10 nurse students and 10 instructors. Reliability was test by Cronbach’s alpha coefficient that was 0.958 and 0.976 sequentially. Data analysis was done by descriptive statistic: frequency, percentage, mean, and standard deviation. The results showed that family nursing competency of student nurses was at high level in all aspects (mean=3.84, SD=0.41). The highest score was competency of family nursing evaluation practice (mean=3.93, SD=0.46). The highest score of specific item was “family nursing effect on health promotion, prevention of illness and restore family health” (mean=4.34, SD=0.75) and the lowest item score was “documentation of statistical data related to family nursing, case recording and creating database related to professional standards correctly and cover” (mean=3.50, SD=0.66). For the instructors perception, the student nurses had the highest competency of enhancing and promoting family health (mean=4.16, SD=0.57). The highest score of specific item was “practicing by awareness of cultural and traditional of each family life style” (mean=4.16, SD=0.67). The lowest item score was the same as student nurses perception (mean=3.45, SD=1.05).In conclusion, most of the student nurses and instructors evaluated the family nursing competency at high level. However, the competency of documentation of statistical data related to family nursing, case recording and creating a database was at the lowest score. Therefore, content and learning process development should be focused for achieving better score of family nursing competency in all aspects and items.